Penerapan Konseling Realita (Wdep) Dalam Meningkatkan Penyesuaian Diri Pada Siswa Smp Yang Kehilangan Ayah (Remaja Yatim) - Amelia Putri Amel; Amy Novalia Esmiati (Psycho Aksara : Jurnal Psikologi, 2024)
The aim of this study was to see the impact of providing the WDEP reality counseling intervention. The subjects of this research were male junior high school students aged 15 years. The assessment used to explore the data as a whole or look for problems that exist within the subject is by conducting observations, interviews and a series of psychological tests. The subject has adjustment problems, these problems arose after his father died. The intervention given for adjustment problems is by providing WDEP reality counseling techniques. The intervention that has been implemented has resulted in the fact that WDEP reality counseling is effective in helping subjects improve self-adjustment, subjects can reduce maladaptive behavior to adaptive, apart from that, based on the evaluation results, it shows that subjects have gradually shown significant changes in behavior. These changes in behavior include the subject no longer being alone at school, but the subject wanting to join his three friends, showing more stable emotions, the subject no longer showing a resistant attitude when reprimanded by the teacher when yawning in class, the subject being active in class, the subject being willing to ask friends when the subject does not understand the teacher's explanation, the subject no longer pollutes the class with the aim of seeking the teacher's attention, the subject is willing to do the teacher's assignments at home and the subject is willing to interact with his family environment and school environment.Keyword: Self-Adjustment, Reality Counseling, WDEP